Determinants of participation in cavy marketing: Evidence from the Democratic Republic of Congo - Simtowe, Franklin; Paul, Birthe K.; Wimba, Benjamin M.M.; Bacigale, Samy B.; Chiuri, Wanjiku L.; Maass, Brigitte L. (Kassel University Press, 2017)
Smallholder supply chain participation remains low despite the potential welfare gains that would result from choosing a market-oriented production. Yet, studies on determinants of market participation for commodities with underdeveloped value chains are scanty. Employing a double-hurdle model, this paper examines factors determining households’ participation in cavy marketing among cavy farmers from Sud-Kivu province in the Democratic Republic of Congo. We Bnd that wealthier households participated less in cavy marketing while those producing more cavies were more likely to participate in their marketing. Moreover, smaller households tended to sell more cavies, while households with other livestock sold fewer cavies. The Bndings underscore the signiBcance of increasing the participation in the cavy supply chains by farmers through the promotion of appropriate husbandry practices that enhance cavy productivity and production and that enable farmers to participate in markets as sellers.